One-step synthesis of a cyclic 2, 17-dioxo[3, 3](4, 4′) biphenylophane and first preparation of a microporous polymer network from a macrocyclic precursor by cyclotrimerization1. Issue 43 (28th May 2015) - Samanta, Suman Kalyan; Preis, Eduard; Lehmann, Christian W.; Goddard, Richard; Bag, Saientan; Maiti, Prabal K.; Brunklaus, Gunther; Scherf, Ullrich
<x xml:space="preserve">Abstract</x> Macrocycle 2, 17-dioxo[3, 3](4, 4′)biphenylophane was synthesized and used in the formation of a microporous polymer network.